PARTICIPATION OF LEADERS AND COMMUNITY IN SOLID WASTE MANAGEMENT IN INDONESIA TO REDUCE LANDFILL WASTE LOAD - Indriyani Rachman; Qiyam Maulana Binu Soesanto; Hafizhul Khair; Toru Matsumoto (Journal of Community Based Environmental Engineering and Management, 2020)
The increase in population and changes in community consumption patterns are one of the triggers for the increasing volume of waste. Therefore, changes are needed to manage waste so that the accumulation of waste can be handled properly. Government cooperation is considered important in solving problems. The volume of waste from its source has to be reduced. Therefore, it is important to empower the community in managing waste. This study compares the community participation in 3 villages in managing waste in their respective housing areas and waste management managed by the City Sanitation Department. Waste management in 3 locations became areas that can reduce the amount of waste going to the landfill. The data collection methods include interviews, observation and documentation, while data analysis uses descriptive qualitative techniques. Based on the results of the study, one form of leader and community participation in environmental improvement efforts is by participating in managing waste, participating in 3R workshops and giving labor contributions in the form of community service.